2012 IEEE Symposium on Business, Engineering and Industrial Applications 2012
DOI: 10.1109/isbeia.2012.6422984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural and synthetic cytokinin hormone on shoot regeneration of rockmelon (Cucumis melo) Glamour cv. by using nodal explants

Abstract: Rockmelon Glamour cv. belongs to Cucurbitaceae family and the fruit enriched with nutrients that can reduce the risk of cancer, heart disease and asthma. Using in vitro culture technique, rockmelon was able to mass propagate and commercially cultivated in order to meet rising market demand. The objectives of this study were to develop a micropropagation protocol for mass production of new Glamour cv. new plantlets and to acclimatize the plantlets to the ex vitro condition for further growth process. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In the previous study on C. annuum L. by [16], it was found that higher concentration of BAP is effective for shoot multiplication in shoot tip explants. Similar observation was also found in other plants such as Jatropha [17], pineapple [18] and rockmelon [19]. While [20] determined that higher concentration of BAP (>2.0 mg/L) would not be effective in shoot regeneration.…”
Section: B Callus Induction and Shoot Regenerationsupporting
confidence: 75%
“…In the previous study on C. annuum L. by [16], it was found that higher concentration of BAP is effective for shoot multiplication in shoot tip explants. Similar observation was also found in other plants such as Jatropha [17], pineapple [18] and rockmelon [19]. While [20] determined that higher concentration of BAP (>2.0 mg/L) would not be effective in shoot regeneration.…”
Section: B Callus Induction and Shoot Regenerationsupporting
confidence: 75%